Quantitative Exposure Metrics for Sleep Disturbance and Their Association With Breast Cancer Risk - Girschik, J.; Fritschi, Lin; Erren, T.; Heyworth, J. (Kluwer Academic Publishers, 2013)
Purpose It has been acknowledged by those in the field of sleep epidemiology that the current measures of sleep used in many epidemiological studies do not adequately capture the complexity and variability of sleep. A number of ways to improve the measurement of sleep have been proposed. This study aimed to assess the relationship between novel ‘sleep disturbance’ metrics, as expanded measures of sleep, and breast cancer risk.Methods Data for this study were derived from a population-based case–control study conducted in Western Australia between 2009 and 2011. Participants completed a self-administered questionnaire that included questions about demographic, reproductive, and lifestyle factors in addition to questions on sleep. Four metrics of exposure to sleep disturbance (cumulative, average, duration, and peak)were developed. Unconditional logistic regression was used to examine the association between metrics of sleep disturbance and breast cancer risk.Results There was no evidence to support an association between any of the sleep disturbance metrics and breast cancer risk. Compared with the reference group of unexposed women, the fully adjusted ORs for cumulative sleep disturbance (harm) metric were as follows: 1st tertile 0.90 (95 % CI: 0.72–1.13); OR for the 2nd tertile 1.04 (95 % CI: 0.84–1.29); and OR for the 3rd tertile 1.02 (95 % CI:0.82–1.27).Conclusions This study found no association between several metrics of sleep disturbance and risk of breast cancer. Our experience with developing metrics of sleep disturbance may be of use to others in sleep epidemiology wishing to expand their scope of sleep measurement.